2021
DOI: 10.1136/bmjgh-2020-004233
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in pregnancy-related deaths: spatial and Bayesian network analyses of maternal mortality ratio in 54 African countries

Abstract: BackgroundMaternal mortality remains a public health problem despite several global efforts. Globally, about 830 women die of pregnancy-related death per day, with more than two-third of these cases occurring in Africa. We examined the spatial distribution of maternal mortality in Africa and explored the influence of SDoH on the spatial distribution.MethodsWe used country-level secondary data of 54 African countries collected between 2006 and 2018 from three databases namely, World Development Indicator, WHO’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Sub-Saharan Africa (SSA) records some of the highest rates of maternal and child mortality. For instance, it is known from the literature that SSA accounts for almost 90% of the global burden of maternal mortality [5]. This high burden of maternal and child mortality in SSA has been linked to several preventable factors including low antenatal care (ANC) utilisation as well as low uptake of postnatal care (PNC), skilled attendant delivery, and health facility delivery [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa (SSA) records some of the highest rates of maternal and child mortality. For instance, it is known from the literature that SSA accounts for almost 90% of the global burden of maternal mortality [5]. This high burden of maternal and child mortality in SSA has been linked to several preventable factors including low antenatal care (ANC) utilisation as well as low uptake of postnatal care (PNC), skilled attendant delivery, and health facility delivery [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, investing in an efficient and reliable transport network could translate into improved access to health facilities by women during and after PLOS GLOBAL PUBLIC HEALTH pregnancy and childbirth and prevent maternal deaths. Similarly, investing in gender equity and empowerment initiatives may help resolve some individual and health facility-level contributing factors [24]. Social scientists using political economy methods explored the explanations for the variations in maternal mortality rates between countries.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…So far, most articles that have explored the relationship between contributory factors and maternal deaths in Africa used statistically modelled population-level data from the WHO Global Health Observatory, Human Development Report, World Bank and United Nations bodies [11,[19][20][21][22][23][24]. A single study utilised primary data from hospital-based studies [25].…”
Section: Introductionmentioning
confidence: 99%
“…The region has a lifetime risk of maternal deaths of 1 in 38 with an estimated 530 000 maternal deaths occurring each year [ 5 ]. Compared with developed countries, Sub-Saharan Africa cumulates many physical, economic, social, and psychological handicaps, especially in its rural areas: scattered settlements, poor health infrastructure, shortage of qualified healthcare personnel, transportation, and health awareness, and low levels of income and education [ 6 , 7 ]. A study by Wilunda et al [ 8 ] reported that access to health services in South Sudan is hampered by a poorly functioning health system that is plagued by chronic problems such as a shortage of human resources, lack of health infrastructure and supplies, and weak management [ 8 ].…”
Section: Introductionmentioning
confidence: 99%